Answer: x= -8
Step-by-step explanation:
Answer:
Option A: -12x-8=10 is the correct answer.
Step-by-step explanation:
Given equation is:
-4 (3x+2) = 10
We will distribute the equation by multiplying the terms inside the brackets with -4.
Therefore,
-4*3x + 2*-4 = 10
-12x +(-8) = 10
-12x - 8 = 10
The equation -4 (3x+2) = 10 will become -12x-8=10 after distributing.
Hence,
Option A: -12x-8=10 is the correct answer.
Answer:
Step-by-step explanation:
If you can post the table then I'lI be happy to help
Answer:
7/12.
Step-by-step explanation:
=x/x+5.
x-5/x+5+4=⅛
x-5/x+9=⅛
x-5=⅛(x+9)
x-5=⅛x+1⅛
x-⅛x=1⅛+5
⅞x=49/8
7x=49
x=7
thus the initial fraction is x/x+5= <u>7</u><u>/</u><u>1</u><u>2</u>
A rational number is a fraction